Influence of Head and Neck Position on Oropharyngeal Leak Pressure and Cuff Position with the ProSeal Laryngeal Mask Airway and the I-Gel: A Randomized Clinical Trial - Sandeep Kumar Mishra; Mohammad Nawaz; M. V. S. Satyapraksh; Satyen Parida; Prasanna Udupi Bidkar; Balachander Hemavathy; Pankaj Kundra (Anesthesiology Research and Practice)
Background. This study was designed to assess and compare the effect of head and neck position on the oropharyngeal leak pressures and cuff position (employing fibreoptic view of the glottis) and ventilation scores between ProSeal LMA and the I-gel. Material and Methods. After induction of anesthesia, the supraglottic device was inserted and ventilation confirmed. The position of the head was randomly changed from neutral to flexion, extension, and lateral rotation (left). The oropharyngeal leak pressures, fibreoptic view of glottis, ventilation scores, and delivered tidal volumes and end tidal CO2 were noted in all positions. Results. In both groups compared with neutral position, oropharyngeal leak pressures were significantly higher with flexion and lower with extension but similar with rotation of head and neck. However the oropharyngeal leak pressure was significantly higher for ProSeal LMA compared with the I-gel in all positions. Peak airway pressures were significantly higher with flexion in both groups (however this did not affect ventilation), lower with extension in ProSeal group, and comparable in I-gel group but did not change significantly with rotation of head and neck in both groups. Conclusion. Effective ventilation can be done with both ProSeal LMA and I-gel with head in all the above positions. ProSeal LMA has a better margin of safety than I-gel due to better sealing pressures except in flexion where the increase in airway pressure is more with the former. Extreme precaution should be taken in flexion position in ProSeal LMA.